KECENDERUNGAN DAN KARAKTERISTIK PENELITIAN SASTRA DALAM SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS TIMOR - Rejo, Uman (Hasta Wiyata, 2024)
This literary study aims to explore, classify, and describe the tendencies and characteristics of literary research in the thesis of students of the Indonesian Language and Literature Education study program at the Faculty of Education, University of Timor. The data source used is the thesis of students of the Indonesian Language and Literature Education study program from 2018—to March 2022. The data was obtained using data owned by the administration of this study program. The data collected will be studied using a qualitative descriptive method with a sociological approach to literature. This approach is not only used to examine literary works from the sociological aspect but can be used to examine the results of literary research which can then be formulated into a concept or characteristic that is unique and unique from the existing tendencies. The results and discussion show as follows. First, student literature research with the object of modern literary works tends to use poetry, short stories texts, short anthologies, films, and novels. Research with this object does not attract the attention of students so only a few examine it. Second, student literature research with oral objects and practices of local traditions dominates. Students tend to use mantras, legends, rituals, traditional stories, cultural symbols, cultural expressions, traditional houses, traditional animals, traditional woven fabrics, and folklore as data in their research. Third, students tend to use a structural or objective approach in their literary research, both in studying modern and oral literature or local traditional practices. The structural approach used tends to focus on separate intrinsic elements so that the resulting meaning is not totality. Fourth, student research with the object of teaching literature in schools still seems monotonous and boring, the media used is too old-school, and has not taken advantage of technological sophistication from 4.0 to 5.0.